Antoine Plante research information, - Heaton, J.
Small collection of research materials on Antoine Plante (ca. 1812-1890) by J. Heaton of Spokane. Mr. Heaton wrote to Plante's descendants, Ben Burgander and Mrs. Duncan McDonald looking for information on Plante. Heaton also wrote a manuscript on Plante, and drew maps of Plante's Ferry.